Registration of two oilseed sunflower germplasms, HA‐R18 and HA‐R19, resistant to sunflower rust. Issue 3 (23rd July 2022) - Qi, Lili; Ma, Guojia; Seiler, Gerald
Abstract: Sunflower rust, incited by the fungus Puccinia helianthi Schwein., is a serious fungal disease in the sunflower ( Helianthus annuus L.) growing areas worldwide, with an increasing importance in North America in recent years due to the frequent evolution of new pathogen races. HA‐R18 (Reg. no. GP‐377, PI 698197) and HA‐R19 (Reg. no. GP‐378, PI 698198) are rust‐resistant germplasm lines that were developed and released cooperatively in 2020 by the USDA‐ARS, Sunflower and Plant Biology Research Unit and the Agricultural Experiment Station of North Dakota State University. The rust resistance in HA‐R18 and HA‐R19 originated from KP193 and KP199, respectively, which were identified segregating for rust resistance after screening of 58 sunflower lines introduced from South Africa. Rust evaluation of HA‐R18 and HA‐R19 with 11 P. helianthi races indicated that both lines exhibited resistance to the most rust races tested including the most predominant and the most virulent races currently identified in the United States. HA‐R18 and HA‐R19 possess the new rust resistance genes R17 and R18, respectively, both of which have been mapped to sunflower chromosome 13. The two new lines will diversify the pool of rust resistance genes and should serve as useful sources of rust resistance in sunflower. Core Ideas: Two oilseed sunflower germplasms resistant to sunflower rust were developed. HA‐R18 and HA‐R19 harbor the new rust R gene R17 and R18, respectively. HA‐R18 and HA‐R19 exhibit resistance to the most prevalent and virulent races of rust.